Maternal Well-Being in Families of Children with Neurodevelopmental Disorders: A Systematic Review Through an Ecological Systems Framework - Ikhwanisifa, Ikhwanisifa; Rauf, Siti Hajar Abdul (Universitas Muhammadiyah Yogyakarta, 2026)
Despite growing research, limited integrative evidence exists on how multilevel determinants shape maternal well-being among families raising children with neurodevelopmental disorders (NDDs), particularly in non-Western contexts. This review aimed to examine how psychological resources, family processes, social support systems, and structural conditions interact to influence maternal well-being. Guided by Bronfenbrenner’s Ecological Systems Theory and the Family Stress Model, this systematic review followed PRISMA 2020 reporting guidelines and synthesized evidence from 34 empirical studies (2021–2026) retrieved from the Scopus database using thematic synthesis. Findings consistently indicate that psychological capital, adaptive coping, and social support emerged as the most frequently reported protective factors across studies. At the same time, caregiving burden, stigma, economic instability, and child behavioral challenges were the most common risk factors. Structural constraints and stigma were more consistently associated with maternal distress than child clinical severity across diverse contexts. These findings suggest that maternal well-being may be understood as a form of developmental infrastructure that supports family functioning and child development across ecological systems. The review highlights the need for culturally responsive, multilevel interventions in Southeast Asia, including strengthening social support systems, reducing stigma, and informing family-centered policies.